Bibliotherapy for Cancer Patients and Their Families - Janavičienė, Daiva (Slauga. Mokslas ir praktika, 2023)
Cancer patients experience severe health issues and the resulting emotional and psychological complications; therefore, in addition to medical treatment, they also need emotional/psychological support. Bibliotherapy is one of the possible ways of support. The study is aimed at developing a concept of bibliotherapy for cancer patients and providing practical recommendations for service organizers. It uses a targeted information search on bibliotherapy services in Lithuanian public libraries and a questionnaire survey. The concept of bibliotherapy is based on the theories of nursing, social work and library of science. Bibliotherapy services for cancer patients can be provided in primary health care settings or public libraries. The bibliotherapy service in libraries must be conducted in cooperation with medical professionals. The bibliotherapy service, which can be didactic/informative bibliotherapy (recommended reading lists), personal development bibliotherapy (reading services in public libraries), and reading groups (clubs), can be organized in public libraries or in institutions that provide emotional/psychological support. A number of reading clubs with elements of bibliotherapy have been introduced in Lithuanian libraries. A similar service has been identified for a target group, i.e., cancer patients. On the one hand, naming the target audience of the club may traumatize the potential beneficiaries of the service, and on the other hand, it allows for better dissemination of information and better access for patients. Cooperation between institutions is needed to enable patients to learn about bibliotherapy and to have more confidence in the service.
Keywords: Reading therapy; Rehabilitation and personal development bibliotherapy; Book recommendations; Library services; Reading clubs; Bibliotherapy in healthcare institutions